Correction: Diagnostic Accuracy of Microscopic Observation Drug Susceptibility (MODS) Assay for Pediatric Tuberculosis in Hanoi, Vietnam. - Tran, S; Renschler, J; Le, H; Dang, H; Dao, T; Pham, A; Nguyen, LT; Van Nguyen, H; Thi Thu Nguyen, T; Ngoc Le, S; Fox, A; Caws, M; et al. (2013)
[This corrects the article on p. e72100 in vol. 8.].